2020
DOI: 10.1177/2158244020914648
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Economic Growth, Energy Consumption, CO2 Emission, and Urbanization: Evidence From MINT Countries

Abstract: This study aimed at examining the synergy among economic growth, carbon dioxide (CO2) emissions, urbanization, and energy consumption in MINT (Mexico, Indonesia, Nigeria, and Turkey) countries. Yearly data from 1993 to 2017, which were sourced from World Bank Development Indicators, were employed, and the analysis was performed by employing the ARDL Bounds test approach. The findings from the study reveal that the energy–growth hypothesis that assumed unidirectional causality from energy consumption was true f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
92
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 56 publications
14
92
0
1
Order By: Relevance
“…Meanwhile, some recent studies tilted their studies towards the investigation of energy types and the implication on carbon emission. The studies supported the arguments that renewable energy and non-renewable energy can be detrimental to the environment [15,52,54,74]. Another recent study for a single country from Shabestari [88] and Sarwar et al [87] for Sweden and China respectively confirmed a positive relationship between energy consumption and carbon emission.…”
Section: Literature Reviewsupporting
confidence: 63%
See 1 more Smart Citation
“…Meanwhile, some recent studies tilted their studies towards the investigation of energy types and the implication on carbon emission. The studies supported the arguments that renewable energy and non-renewable energy can be detrimental to the environment [15,52,54,74]. Another recent study for a single country from Shabestari [88] and Sarwar et al [87] for Sweden and China respectively confirmed a positive relationship between energy consumption and carbon emission.…”
Section: Literature Reviewsupporting
confidence: 63%
“…The studies on the relationship between economic growth and carbon emission in the literature have been mixed. While some studies presented a unidirectional relationship between economic growth and carbon emission [7,10,16 [65,74,85,88]. Though, few of them concludes in their studies that no causality exists between economic growth and carbon emission (Jardon et al 2017; [87,109].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Akin (2014) revealed that there is an uni-directional relationship running from CO2 emission and trade while Ertugrul et al (2016) study shows that there is an uni-directional relationship running from trade and CO2 emission. Several studies have included urbanization in their model (Khoshnevis & Dariani, 2019;Abbas, 2020;Kasman & Duman, 2015;Odugbesan & Rjoub 2020). Khoshnevis & Dariani (2019) reveal that the link between urbanization and GDP growth is bi-directional while Abbasi et al (2020) researched 8 Asian countries and finding revealed a bidirectional relationship between urbanization and energy consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Odugbesan & Rjoub (2020) utilize the time series data set to examine the link between economic growth, energy consumption, urbanization and CO2 emissions on MINT economies. Contrary to Odugbesan & Rjoub (2020), this study employed the panel data set to examine the relationship between economic growth, energy consumption, urbanization and CO2 emissions. Also, trade was incorporated into the model, which will help in filling the gap in energy and environmental literature concerning countries with similar features such as MINT.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation